Effect of some nutrients on the health statue of iron anemic rats - Shahin, Kh. A.; Abd Elkhalek, Mai; Eltatawy, Asmaa H. (2015)
The main objective of this study is to evaluate the interaction effects of some nutritional elements in healthy status of rats induced by iron deficiency anemia. A total of 60 male albino rats weighing (120±10g) were used in this study .Rats were divided into 6 groups, the first control negative group, other groups was induced by iron deficiency anemia as fed on 20 mg of tannic acid for 21 frequency days, these anemic ratsfed on standard diet and high dietary iron source as liveralong studying period and divided into follow groups, the second control positive group. Third group fed on high dietary iron source as liver only. Fourth group supplemented with sucrose (13.8% of the diet). Fifth groupsupplemented with vitamin A(4500 IU/kg feed).Sixth groupsupplemented with calcium (1.2% of diet)for 28 days. The results showed that there was a significant increase in serum iron among treated groups after dietary intervention, especial in liver plus vitamin A group. . For serum ferritine, comparative effect stated that liver plus sucrose group had the nearest mean to negative control group. While liver plus calcium group had insignificant differed to positive control group.
Includes reference
Summary in arabic.
1
Keywords: Rats as laboratory animals -- Experiments; Anemia; Calcium -- Physiological effect; Vitamin A -- Physiological effect; Sucrose -- Physiological effect